Analisis Image Noise dan Dosis pada Pemeriksaan MSCT dengan Menerapkan Aplikasi Piranti Lunak Care Dose Pesawat Siemens Somatom 6 Slice di RSUD Prof. Dr. Margono soekarjo purwokerto - Lutfatul Fitriana; Gatot Murti Wibowo; Sudiono Sudiono (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: Multi-Slice Computed Tomography (MSCT) is diagnostic radiology examination that take an advantage of computer to acquire data and reconstructing an Image from number of detector rows. Noise is one of the tremendous factors that affect the quality of CT Images. Nowadays, CT mAs auto setting, an automatic exposure device, resolves such the Noise problems in which maintains the quality of diagnostic Images for all parts of the body with a lowest possible dose. Since working devices based on the size of the patient's body attenuation automatically, reduction of radiation dose by 40% to 50% would be achieved. Yet, the larger patient’s body parts, the higher patient’s CTDIvol occurrence, which in turn affects on the Noise produced.  The purpose of this research is to define the difference in the value of Image Noise and dose whenever the MSCT procedure is employed with and without the auto mAs selection with regards to maintaining CTDIvol and Image Noise.Methods: This research was an experimental quantitative study with one shot case study and post-test only approaches. Data were collected on July 2016 in Radiology Unit of Prof. Dr. Margono Soekarjo Purwokerto Hospital. Noise values was measured on 20 mm region of interest (ROI) and the dose was calculated by the CTDIvol on the workstation monitor were collecting data from the head, thorax and abdomen water phantom of CT Images. Data was analyzed by SPSS 16 software using statistical tests of the paired t-test.Results: The results of this study statistically deemed significant as there were differences in Image Noise values such as head, thorax and abdomen water phantoms (value ρ - value 0.05). Similarly, figures about the CTDIvol comparison also showed different dose levels received by the phantoms when apply the CT procedures with and without auto mAs selection to the head, thorax and abdomen water phantoms (the head phantom: 50.69 mGy Vs. 60.28 mGy; the thoracic phantom: 3.88 mGy Vs. 7,98 mGy; and the abdomen phantom: 8.38 mGy Vs. 20.83 mGy respectively). Conclusion: There was a difference in production of the Image Noise and dose when apply the CT procedures with and without auto mAs selection to the head, thorax, and abdomen water phantoms. Lower dose tended to induce more Noise than higher dose, meanwhile patient’s dose leads to increase as well.